Leveraging Generative AI for Automated Performance Optimization: A Technical Deep Dive - Sai Ram Chappidi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the evolution and current state of performance optimization in modern technological systems, focusing on the transformative impact of generative AI and quantum computing. The article examines the progression from traditional manual optimization methods to advanced AI-driven approaches, highlighting improvements in data center operations, enterprise systems, and deep learning architectures. The article investigates the emergence of autonomous systems, adaptive learning capabilities, and the integration of quantum computing in optimization processes. Furthermore, it addresses critical ethical considerations in AI-driven optimization, including transparency, human oversight, and bias mitigation, while emphasizing the importance of balanced governance frameworks for sustainable technological advancement.
Keywords: Performance Optimization; Generative AI; Quantum Computing; Ethical AI Governance; Adaptive Learning Systems